2023
DOI: 10.35870/emt.v7i1.843
|View full text |Cite
|
Sign up to set email alerts
|

Peran Diferensiasi Produk Mobil Nissan Terhadap Minat Beli Konsumen pada PT. Wahana Rejeki Mobilindo Cirebon Cabang Indramayu

Abstract: The technological development of the Indonesian people has brought about major changes in both the infrastructure that supports the lives of the Indonesian people and the quality of life of the people themselves. Expressways as a land transportation infrastructure for the people of Indonesia have undergone rapid development as evidenced by the emergence of various expressways connecting one city to another. Wheeled vehicles or cars as means of transportation have played an important role in society. The state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Furthermore, (Susanto & Rahmi, 2013) also found that product differentiation has a significant influence on consumer purchase intention. (Yudianto & Nurpratama, 2023) further support these findings by suggesting that product differentiation has a positive influence on consumer purchase intention. On the other hand, (Ramdini & Ismunandar, 2020) state that there is no significant influence between product differentiation and consumer purchase intention.…”
Section: The Influence Of Product Differentiation On Customer Purchas...supporting
confidence: 65%
“…Furthermore, (Susanto & Rahmi, 2013) also found that product differentiation has a significant influence on consumer purchase intention. (Yudianto & Nurpratama, 2023) further support these findings by suggesting that product differentiation has a positive influence on consumer purchase intention. On the other hand, (Ramdini & Ismunandar, 2020) state that there is no significant influence between product differentiation and consumer purchase intention.…”
Section: The Influence Of Product Differentiation On Customer Purchas...supporting
confidence: 65%